2018
DOI: 10.1016/j.drugpo.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The perspectives of structurally vulnerable people who use drugs on volunteer stipends and work experiences provided through a drug user organization: Opportunities and limitations

Abstract: Low threshold employment opportunities within DUO may provide significant individual and public health benefits. However, these benefits are constrained by the small size of stipends. Therefore, to ensure better inclusion of PWUD, our findings recommend the development and expansion of equitable, accessible, well-paying employment programs for PWUD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 41 publications
(52 reference statements)
4
27
0
Order By: Relevance
“…Consistent with previous studies demonstrating the non-material benefits of peer worker positions in drug user organizations and harm reduction programming, including empowerment and enhanced authority (Bardwell et al, 2018a;Buchman et al, 2018;Greer et al, 2018;Marshall et al, 2017), our findings illustrate how involving peers as workers in OPS programming provided formal recognition of the unique expertise of PWUD while also enabling these individuals to enhance their skillsets and employability. As such, this approach served to mitigate the tokenization that some peers have described in relation to their engagement in other harm reduction interventions (Greer et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with previous studies demonstrating the non-material benefits of peer worker positions in drug user organizations and harm reduction programming, including empowerment and enhanced authority (Bardwell et al, 2018a;Buchman et al, 2018;Greer et al, 2018;Marshall et al, 2017), our findings illustrate how involving peers as workers in OPS programming provided formal recognition of the unique expertise of PWUD while also enabling these individuals to enhance their skillsets and employability. As such, this approach served to mitigate the tokenization that some peers have described in relation to their engagement in other harm reduction interventions (Greer et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
“…However, given that Vancouver has a well-established system of drug user organizations and peer-based programming that was harnessed to support this response, this approach may be less feasible in settings where peers are not already actively engaged in the delivery of such services. Thus, our findings underscore the need for adequate funding to support drug user organizations and other peerbased initiatives (Bardwell et al, 2018a;Greer et al, 2018), as these appear to be critical in ensuring community capacity for successful peer-driven responses to the overdose epidemic. In addition, future research should seek to explore the role of various factors, including lack of established drug user organizations, in influencing peer worker involvement in OPS programming and related outcomes in diverse settings.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Our study found that experiential workers are constantly dealing with the loss of loved ones due to the overdose crisis, which imposes an emotional toll on them. This nding is in line with other studies demonstrating that the overdose crisis has led to considerable grief for PWUD [11,[20][21][22]. Exposure to such trauma leads to distress and is termed "compassion fatigue" [72].…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have shown that working in overdose response settings can be stressful and traumatizing, with lasting social, emotional and mental health effects for individuals [11,[18][19][20][21][22]. Individuals working in overdose response face grief due to the signi cant loss of lives during the overdose epidemic [11,[20][21][22]. A recent study indicated that even a single exposure to a fatal or non-fatal overdose can lead to considerable stress, burnout and overdose-related compassion fatigue [23].…”
Section: Introductionmentioning
confidence: 99%